BASIC PRINCIPLES OF THE COGNITIVE COMPONENT OF THE ARTISTIC AND PEDAGOGICAL COMPETENCE OF THE FUTURE TEACHER OF FINE ARTS (Pedagogy of Higher and Secondary Education, 2009)
The article reveals the gist of cognitive competence of artistic pedagogical competence of the future art teacher.
Keywords: competence and competence; artistic and pedagogical competence